PENYULUHAN HUKUM PENCEGAHAN KENAKALAN REMAJA (NARKOBA, PERUNDUNGAN, MIRAS) PADA SISWA-SISWI SMP NEGERI 1 MERAUKE - Pieter, Salvadoris; Endom, Agustina Handayani Winingsih; Ayu, Cica Kusmira Sagita; Imkotta, Betsy Rachel; Fenetiruma, Raymond Paradeys (Astha Grafika, 2025)
This community service initiative was motivated by the increasing vulnerability of adolescents in Merauke Regency to the dangers of narcotics, bullying, and alcohol abuse due to a lack of legal literacy. This activity aims to provide a comprehensive understanding of the law and foster preventive awareness among students at SMP Negeri 1 Merauke. The implementation method used a juridical-educational approach through the